METODE QUALITY FUNCTION DEPLOYMENT (QFD) UNTUK INFORMASI PENYEMPURNAAN PERAKITAN VARIETAS MELON - Yayah Wagiono; Hamrah Hamrah (Departemen Agribisnis, FEM-IPB, 2007)
Problems faced by the development of melon fruit in Indonesia are closely related to the domestic availability of seed. Although the government research center as well as private seed producers have been able to produce melon seed, the largest part of the seed supply is still imported. The objectives of this study are to pursue or to identify ideotype of melon that the domestic consumers is willing to consume and to apply QFD methods (to compose HOQ matrix) in developing domestic melon seed breeding.The melon fruit demanded by institutional consumers is the melon fruit without net, and demanded melon fruit by the final consumers is the netted melon fruit. The application of QFD in the planning of the melon varieties is started by composing the HOQ matrix that consisted of the following steps: first, to compose the customers conditions; second, to compose the technical conditions; third, to develop the relationship between the customers and technical condition; fourth, to evaluate the technical competitiveness; fifth, to develop the technical conditions; sixth, to develop the customers condition, and finally, to develop the priority of technical conditions. The recommendation given to the melon seed breeders is to concentrate on the technical conditions with the highest absolute and relative weighted values.